Determinants Of Employees' Job Performance In Small And Medium Enterprises (Smes) : The Moderating Impact Of Organizational Culture - Pui, Wan Jin (Universiti Malaysia Sarawak (UNIMAS), 2017)
This research was conducted to investigate the relationship between employees' job performance and its determinants. 165 questionnaires were collected from the respondents with executive level or above that worked under small and medium enterprise in Malaysia. In this study, the findings indicated two variables are significantly and positively related to employees' job performance. However, the other three variables were found with no significant effect towards employees' job performance. Furthermore, organizational culture does not moderate the relationship between employees' job performance and its determinants. Nevertheless, the moderator had possessed a positive direct effect that significant towards employees' job performance. Last but not least, the finding is further justified in the last chapter by discussing the consistency of the current study with past research.